Association of Body Mass Index With Somatic Mutations in Breast Cancer - Chen, Bo; Guo, Liping; Li, Kai; Xiao, Weikai; Li, Yingzi; Li, Cheukfai; Mok, Hsiaopei; Cao, Li; Lin, Jiali; Wei, Guangnan; Zhang, Guochun; Liao, Ning (Frontiers in Oncology, 2021)
BACKGROUND: Association between body mass index (BMI) and breast cancer patients’ prognosis or treatment response were demonstrated in previous studies, but the somatic mutations profiles in breast cancer patients with different BMI have not been explored. METHODS: A total of 421 breast cancer patients were included in the study. Capture-based targeted sequencing was performed using a panel consisting of 520 cancer-related genes. RESULTS: A total of 3547 mutations were detected in 390 genes from 421 patients. Tumors of breast cancer patients with different BMI status have similar high-frequency mutation genes and tumor mutation burden. TP53 was the most prevalent gene in the three groups, followed by PIK3CA, ERBB2, and CDK12. Meanwhile, the mutation hotspot of TP53 and PIK3CA also the same in the three BMI groups. More genomic alterations in JAK1 were found in underweight patients. Except for JAK1, differentially mutation genes in postmenopausal patients were completely different from that in premenopausal patients. The distribution of mutation types was significantly different between different BMI groups in postmenopausal group. Underweight patients in postmenopausal group had more TP53 mutation, more amplification and more mutations in genes involved in WNT signaling pathway. CONCLUSIONS: Our NGS-based gene panel analysis reveals the genomic profiling in breast cancer patients with different BMI. Although similar high-frequency mutation genes and tumor mutation burden were found in different BMI groups, some subtle differences could not be ignored. Genomic alterations in JAK1 might play a vital role in underweight breast cancer patients’ progression, which need further study to prove. Postmenopausal underweight breast cancer patients with more aggressive characteristics, such as TP53 mutation, more amplification and more mutations in genes involved in WNT signaling pathway. This study provides a new evidence for understanding the characteristics of breast cancer patients with different BMI.